Life on the edge - Dobson, James C., 1936- (Dallas : Word Pub., 1995)
Provides scriptural foundations on which high school seniors can base crucial decisions about their future lives.
Includes bibliographical references (p. 287-291).
Keywords: Life change events -- Psychological aspects; Life change events -- Religious aspects -- Christianity; Teenagers -- Conduct of life; Young adults -- Conduct of life; Teenagers -- Religious life; Young adults -- Religious life; Conduct of life; Christian life